1999
DOI: 10.1016/s0029-7844(98)00543-2
|View full text |Cite
|
Sign up to set email alerts
|

Population-based screening for postpartum depression*1

Abstract: More than 11% of women had elevated scores on the Edinburgh Postnatal Depression Scale, indicating a high likelihood of postpartum depression and the need for further assessment. The screening process required little extra time and was acceptable to the subjects and clinicians. Screening for postpartum depression is appropriate and feasible for clinical practice and increases the identification of women suffering from this serious, common, and highly treatable disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…We reviewed PPD screening programs described in the English language peer-reviewed literature between 1998 and 2011 [2024, 2732]. Studies were identified from Medline/PubMed, PsychINFO, and Cinahl using title, abstract and keyword searches for the terms “postpartum depression,” “maternal depression,” and “perinatal depression,” each independently and then linked to “screening.” We also identified work published in the same time frame from the references in the Institute of Medicine's (IOM's) report on parental depression [1].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We reviewed PPD screening programs described in the English language peer-reviewed literature between 1998 and 2011 [2024, 2732]. Studies were identified from Medline/PubMed, PsychINFO, and Cinahl using title, abstract and keyword searches for the terms “postpartum depression,” “maternal depression,” and “perinatal depression,” each independently and then linked to “screening.” We also identified work published in the same time frame from the references in the Institute of Medicine's (IOM's) report on parental depression [1].…”
Section: Methodsmentioning
confidence: 99%
“…For example, the screening programs in Australia, New Jersey, and Olmsted County, MN, US [23, 24, 2832] did not report any specific follow-up procedures for further evaluation of elevated screening scores. In three programs procedures for evaluation of women with elevated screening scores required referral to an offsite mental health clinics or to delayed visits to staff at the screening site [20, 22, 33].…”
Section: Program Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In its summary, the U.S. Preventive Services Task Force recommended screening for depression only if further diagnostic and treatment procedures are in place to follow up on screening results (9). To our knowledge, the one study that specifically addressed screening perinatal women for depression (10,11) found that it led to higher detection and treatment rates. Of note is that the women in this cohort had incomes and education levels that were above the national average, and procedures took place in a large multispecialty health care group that had resources for mental health care.…”
mentioning
confidence: 99%
“…In its summary, the U.S. Preventive Services Task Force recommended screening for depression only if further diagnostic and treatment procedures are in place to follow up on screening results (9). To our knowledge, the one study that specifically addressed screening perinatal women for depression (10,11) found that it led to higher detection and treatment rates. Of note is that the women in this cohort had incomes and education levels that were above the national average, and procedures took place in a large multispecialty health care group that had resources for mental health care.…”
mentioning
confidence: 99%